Gender dan Pengembangan Pemikiran Pendidikan Islam - Yu’timaalahuyatazaka, Yu’timaalahuyatazaka (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
This article contains the explanation of gender discourse in thinking development of Islamic education, and it is found some problems of injustice that are needed the right solutions to overcome them. The fundamental problem of gender on the level of epistemology-methodology to develop the islamic education on the basis of this gender is to reconstruct them in the epistemology aspect of islamic education. The educators and learners need to change their paradigm and mindset of sensitive gender. This article is also has explanation of methodology of Islamic education on the basis of integration approaches, normative, historical and intuitive approaches to respond some gender issues in learning process.